Liberal Islam versus Moderate Islam: Elusive Moderates and the Siege Mentality (American Journal of Islam and Society, 2005)
There is a tendency to equate liberal Islam with moderate Islam. Yet thereare occasions when to be liberal demands a sense of outrage and rebellion.The causes of the political radicalization of Islam are different from theroots of theological conservatism. For decades, the Royal House of SaudiArabia has been theologically conservative but not politically radical.Indeed, for a long time the monarchy in Riyadh was a classic example ofhow a Muslim regime could be politically pro-western without being culturallywesternized. Was the Saudi regime politically moderate withoutbeing doctrinally liberal?This journal debate has been rich in trying to diagnose the nature ofIslam’s radicalization, but relatively thin in diagnosing its causes. The bestdiagnosis of these causes in this collection comes from Graham E. Fuller:The Muslim world, feeling itself under siege, and with its sensitivitiesheightened by its witness of the struggle of Muslims right across the globalummah, is not currently operating in an environment conducive toeither intellectual openness or to liberal and reformist thought. TheMuslim world is simply hunkered down in a defensive and survivalistmode. Indeed, the forces of terrorism in the Muslim world must bebrought to heel. But this will not happen unless we see a change in hegemonisticAmerican policies, the explicit American embrace of Israeliright-wing policies in the occupied West Bank, and the linkage withAmerican fundamentalist Christian attitudes.I have never heard the problem better formulated. Indeed, there areglobal causes of Islamic radicalism and global reasons why “Muslim terrorism”has gone international. One factor is the “Latin Americanization” ...